Emotional reactivity and explicit emotional memory biases in major depressive disorder during euthymia. (March 2020) - Bogie, Bryce J. M.; Kapczinski, Flávio P.; McCabe, Randi E.; McKinnon, Margaret C.; Frey, Benicio N.
Highlights: Euthymic MDD participants do not differ from HCs on emotional reactivity (ER). Euthymic MDD participants do not differ from HCs on explicit emotional memory (EM). ER and EM may represent unique cognitive phenomena that are unaffected in MDD during euthymia. Abstract: Major depressive disorder (MDD) is associated with information processing deficits across several cognitive domains. Two examples include biased reactivity (e.g., emotional arousal/reaction) to, and explicit (episodic) memory for, emotional information. Recent research suggests that, compared to healthy controls (HCs), acute depressive states may be associated with reduced reactivity to emotional information in the absence of explicit emotional memory biases; however, our understanding of the cognitive phenotypes of these phenomena during euthymia (i.e., clinical remission) remain unclear. Sixty-one participants completed the current study (30 euthymic MDD, 31 matched HCs). Participants rated the emotional intensity (i.e., emotional reactivity) of 48 negative, 48 neutral, and 48 positive images before returning one week later for a surprise recognition memory task. We found main effects of valence across analyses of the emotional reactivity and memory data, such that: (1) both groups displayed higher mean intensity ratings for negative versus positive images ( p  < 0.0001), for positive versus neutral images ( p  < 0.0001), and for negative versus neutral images ( p  < 0.0001); (2) both groups displayed reduced memory sensitivity (e.g., the ability to accurately discriminate between signal (i.e., old stimuli) and noise (i.e., new stimuli) for positive compared to neutral ( p  = 0.007) and negative ( p  = 0.03) images; and (3) both groups displayed reduced normalized memory sensitivity for positive versus negative images ( p  = 0.006). The euthymic MDD group did not differ from the HC group on emotional reactivity or emotional memory performance. These findings contribute to growing evidence that emotional reactivity and explicit emotional memory may not be affected in individuals with MDD during euthymia.